Real worlds, possible worlds and lexical borrowing. A proposal to the plurality of the real world - Giraldo Gallego, Diana Andrea (Estudios de Filosofía, 2014)
The presence of loan words in a language is an indication of the introduction of a foreign word and of a new reality. Here I will discuss how the presence of loan words in languages is a sign of the plurality of the real world. For this, I follow from the thesis put forward by Lewis (1986) on the plurality of worlds and introduce examples of Muisca and Spanish, as proof that the world, as a unique place where everything is included, carries within it the plurality of the real world because there is often another that is unknown and therefore cannot be within its possible worlds.